KONTRIBUSI PEMANFAATAN PERPUSTAKAAN JURUSAN TEKNIK SIPIL TERHADAP PENYELESAIAN SKRIPSI PADA MAHASISWA PENDIDIKAN TEKNIK BANGUNAN FT UNP - 2158-2163, Raei Donni Nalis (CIVED, 2018)
Abstract—This research started from many student  takes a long time in completing the thesis. This type of researchin descriptive correlational research with quantitative approach.Sampling technique using Total sample of 31 students. Data collected by using questionnaire with Likert Scale consisting of 4 answer choices. The total of questionnaire items in library utilization variable (X) is 21 points and thesis completion variable (Y) is 18 point. Data analysis techniques include: descriptive data, test requirements analysis and hypothesis testing.The result of research proves that there is contribution of library utilization ofstudents’s Civil Engineering Department to the completion thesis of Student’s Building Engineering of FT UNP. The correlation coefficient is 0,736, ttest  the value of significance is 5,73 greater than ttable 1,69913 and library utilization contribution is 54,17% on completion of thesis.